Living restricted lives - Understanding the impact of isolation, social distancing and other restriction measures on older care home residents and their relatives in England during the COVID-19 pandemic: A qualitative study. - Sarah Sims; Amit Desai; Ruth Harris; Anne Marie Rafferty; Shereen Hussein; Richard Adams; Lindsay Rees; Sally Brearley; Joanne M Fitzpatrick (PLoS ONE)
Background During the COVID-19 pandemic, care homes for older adults in England implemented isolation, social distancing and other restriction measures to help protect residents from contracting the virus. Little was known about the physical and psychological impacts that these measures would have upon residents and their relatives. Aim To explore the experiences of residents and their relatives of living restricted lives during the pandemic. Methods This qualitative study was conducted as part of a 12-month, mixed-methods, phased design. From six purposively sampled care homes in England, 17 purposively sampled residents (all older adults) and 17 purposively sampled relatives participated in an individual, on-line interview, where they discussed their experiences of the restrictive measures implemented within their care home. Interviews were audio- and video-recorded with participants' permission and analysed using an inductive orientation to thematic analysis, with coding and theme development driven by the data content. Results Participants' experiences of care home restrictions varied; their impact was influenced by the existing pattern of relationships that residents and their relatives maintained within and beyond the care home. It was further influenced by the fact that many residents and relatives were still learning how to manage their relationships in the new context of living in a care home. Social distancing measures made care homes feel less homely and denied residents, staff and relatives physical touch and other forms of non-verbal communication. Many residents expressed a broad sense of gratitude that was associated with safety and well-being beyond the pandemic. As older adults, they put the pandemic, and its associated restrictions, within the larger context of their lives. Conclusions Learning from the COVID-19 pandemic is paramount for governments, societies, policy makers, care home providers, care homes and their staff, residents and their families and friends, and researchers. Our study makes an important contribution as one of the first to study the impact of implementing isolation, social distancing and other restrictive measures for care home residents and their relatives in England.